Analisa Temperatur dan Waktu Terhadap Hasil Bahan Bakar Minyak Dengan Proses Pirolisis Sampah Kantong Plastik - Novarini; Darmuji; Hilda Porawati (LPPM Politeknik Jambi, 2018)
Plastic bag type waste is a type of Low-Density Poly Ethylene (LDPE) plastic waste whose presence in Talang Gulo Final Disposal Site in Jambi City is not touched by scavengers because it cannot be resold. This condition resulted in the destruction of this type of plastic bag waste by burning it. Destruction of plastic waste by means of incineration is risky to the environment because pollutants will emit pollutants from CO2, CO, NOx, and SOx exhaust emissions as well as some other pollutants in addition to the general nature of plastic waste which cannot be decomposed by microorganisms on the ground. Efforts to minimize environmental pollution due to plastic bag type waste will be processed using a pyrolysis method using a reactor with temperatures of 250ºC - 450ºC and 65 psi - 65 psi as well as energy-efficient condensers that have high thermal conductivity to produce fuel oil as energy sources. The maximum volume of fuel oil is obtained by a 6hour pyrolysis time of 2,560 ml at a temperature of 450 ºC. The test results for density parameters, specific gravity, water content, flash point, and heating value indicate that the fuel produced meets Indonesian fuel quality standards.